A screening method of oil-soluble synthetic dyes in chilli products based on multi-wavelength chromatographic fingerprints comparison. (1st February 2016) - Zhu, Yonghong; Wu, Yanlei; Zhou, Chunjie; Zhao, Bo; Yun, Wen; Huang, Siyu; Tao, Peng; Tu, Dawei; Chen, Shiqi
Highlights: A HPLC fingerprints comparison method for screening synthetic dyes was proposed. A simple HPLC and sample extraction condition was chosen for fingerprinting. Different chilli product fingerprints had a relatively stable peak profiles. 16 synthetic dyes were used as model analytes to assess the screening efficiency. LOD of the screening method ranged from 0.40 mg/kg to 2.41 mg/kg. Abstract: A multi-wavelength HPLC fingerprint comparison method was proposed for the screening of oil-soluble synthetic dyes in chilli products. The screening was based on the fingerprint differences of normal unadulterated chilli sample with tested chilli samples. The samples were extracted with acetone and fingerprinted by HPLC under four visible light wavelengths (450 nm, 490 nm, 520 nm, and 620 nm). It was found that the fingerprints of different chilli product samples had a relatively fixed number of peaks and stable retention time. When 16 kinds of known synthetic dyes were used as model analytes to assess the screening efficiency, 14 of them could be screened using fingerprint comparison method, with LOD of 0.40–2.41 mg/kg. The new screening method was simple and had the possibility of finding existence of the adulterated dyes which could not be identified using known standard analytes as control.